STUDI DESKRIPTIF PELAKSANAAN SENSUS HARIAN RAWAT INAP RUMAH SAKIT BHAYANGKARA TINGKAT III HOEGENG IMAN SANTOSO BANJARMASIN - Yunita, Nirma; Anhar, Aus Al; Ningsih, Eka Rahma (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
Inaccurate filling of the daily inpatient census impacts the discrepancy in the hospital's performance (statistics). This study aims to examine the daily inpatient census at Bhayangkara Level III Hospital Hoegeng Iman Santoso Banjarmasin. This research uses a qualitative study with a descriptive approach, collecting data through observation and interviews. The subjects of this study are 7 individuals, including the Head of the Medical Records Unit, the Head of the Care Room, and IT staff. The results show that the implementation of the daily inpatient census involves one person responsible for each care room, while the daily census recap is performed by one person from the medical records department. The quality of census officers has been enhanced through training and socialization on how to manually fill out the inpatient daily census. The last education of the medical record staff responsible for the daily inpatient census recap is a DIII in medical records. The daily manual census recap is done using Microsoft Excel. The machine used for the daily inpatient census meets the needs of the staff. Additionally, there is a Standard Operating Procedure (SOP) for the manual daily census, but none for the SIMRS daily census. The implementation of the manual inpatient daily census does not fully comply with the hospital's SOP, as some staff inconsistently record the census for more than 24 hours. Materials used include Microsoft Excel with a daily census format created by the head of the medical records unit.